Blockchain and its Potential in Strengthening Islamic Economic Law - Mufadhol Mufadhol; Widya Khaidir; Lie Jie; Cai Jixiong (Yayasan Adra Karima Hubbi, 2024)
Various aspects of life, including economics and law, have been greatly influenced by advances in information technology. Blockchain is one of the most popular technological innovations today. The technology known as blockchain allows digital transactions to be recorded securely and transparently without the use of intermediaries. This research examines the potential for using blockchain technology to strengthen Islamic economic law. Specifically, this research seeks to find out how blockchain features can support sharia principles such as transparency, fairness and honesty in economic transactions. Apart from that, this research also examines the challenges and opportunities of implementing blockchain technology in a human-based economic system. This study uses qualitative methodology and literature study. The data used in this research was obtained from various secondary sources, such as books, research reports, scientific journals, and articles related to the topic of blockchain and Islamic economic law. The research results show that blockchain has several characteristics that can support Islamic economic law. The main components of transaction records, such as transparency and immutability, can ensure that all transactions are carried out honestly and in accordance with sharia principles. In addition, blockchain technology allows automatic transactions that comply with Islamic law, such as mudharabah contracts and buying and selling. However, this research found several problems. This research finds that blockchain can help implement Islamic economic law by increasing honesty, transparency and fairness in transactions. This technology can help ensure that sharia rules are applied consistently in various forms of economic transactions. However, to fully exploit this potential, governments, academics and practitioners must work together to address existing problems.